Genome-wide analysis of Collo Nudo Italiana and Millefiori Piemontese local chicken breeds: genetic variability and structure analysis in the context of Italian chicken biodiversity - Francesco Perini; Filippo Cendron; Cesare Castellini; Nicolaia Iaffaldano; Margherita Marzoni; Arianna Buccioni; Dominga Soglia; Achille Schiavone; Silvia Cerolini; Emiliano Lasagna; Martino Cassandro; Mauro Penasa (Italian Journal of Animal Science)
This study aimed to assess the genetic diversity and population structure of two Italian local chicken breeds, Millefiori Piemontese (PMP) and Collo Nudo Italiana (PCI), using the 600K Affymetrix SNP chip array, and to contextualise these breeds in the national biodiversity landscape based on 23 Italian local chicken breeds previously characterised. Minor allele frequency (MAF), expected heterozygosity (He), and observed heterozygosity (Ho) of PCI were 0.311 ± 0.170, 0.484 ± 0.107, and 0.469 ± 0.128, respectively. The inbreeding coefficient (FHOM) was −0.001 ± 0.066 and the inbreeding coefficient calculated on runs of homozygosity (ROH) values (FROH) was 0.003 ± 0.004. The PMP had MAF, He, and Ho of 0.245 ± 0.201, 0.383 ± 0.112, and 0.428 ± 0.149, respectively, and exhibited higher FHOM (0.149 ± 0.405) and FROH (0.016 ± 0.009) than PCI. The multi-dimensional scaling plot and neighbour-joining tree depicted clear genetic clustering for both the PCI and PMP breeds. The ROH analysis identified key genomic regions with significant gene annotations. In particular, four ROH islands in GGA4, GGA5, and GGA8 of PCI, and three ROH islands in GGA3 of PMP were detected. For PCI, ROH regions contained genes related to immune response and thermoregulation, such as S1PR1 and PLA2G4A. For PMP, ROH regions included genes involved in muscle development and immune response, such as RRM2, KLF11, and CPSF3. This research provided insights into the genetic diversity and adaptive traits of PCI and PMP breeds, contributing to widen the understanding of Italian local chicken genetic resources.